1998
DOI: 10.1136/bjo.82.12.1416
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and scintigraphic comparison of silicone and polyvinylpyrrolidone coated silicone perforated plugs

Abstract: Background/aim-Isolated stenosis of the lacrimal punctum is a frequent cause of epiphora. Treatment relies on surgical opening or dilatation with bi-or monocanalicular prosthesis. Recently, silicone perforated punctum plugs (PPP) were proposed. The drawback with these silicone PPP was that secretions accumulate in the central orifice blocking the spontaneous flow of tears. A modification of the surface of the PPP using polyvinylpyrrolidone (PVP) was thus proposed. The aim was to compare silicone PPP with new P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
(2 reference statements)
0
11
0
2
Order By: Relevance
“…Pure punctum stenosis treatment relies on punctum dilatation, surgical opening or punctum stenting with canalicular tubes or punctum plugs. However canalicular tubing is unnecessary if there is no intracanalicular pathology 5,6,8–12 …”
Section: Introductionmentioning
confidence: 99%
“…Pure punctum stenosis treatment relies on punctum dilatation, surgical opening or punctum stenting with canalicular tubes or punctum plugs. However canalicular tubing is unnecessary if there is no intracanalicular pathology 5,6,8–12 …”
Section: Introductionmentioning
confidence: 99%
“…Einige verfügen über eine zusätzliche PVP-Beschichtung. Einen Vorteil der PVP-Beschichtung scheint es zumindest bei perforierten Punctum Plugs zu geben [45]. Hier scheint die PVP-Beschichtung zu einer besseren Durchgängigkeit und damit zu einer erhöhten Reduktion der Epiphorasymptomatik zu führen [45].…”
Section: Diskussionunclassified
“…Einen Vorteil der PVP-Beschichtung scheint es zumindest bei perforierten Punctum Plugs zu geben [45]. Hier scheint die PVP-Beschichtung zu einer besseren Durchgängigkeit und damit zu einer erhöhten Reduktion der Epiphorasymptomatik zu führen [45]. Für andere Intubate dagegen ist der Vorteil einer PVP-Beschichtung nicht eindeutig belegt oder gar nicht untersucht.…”
Section: Diskussionunclassified
“…Malet et al 14 reported success in 75% of cases demonstrating acquired punctal stenosis with PVP-coated PPP after 6 months of follow-up. In this study, the plugs were left in place for 2 months, and a patency rate of 84.1% was achieved after a mean follow-up period of 19 months, demonstrating a satisfactory long-term success rate.…”
Section: Discussionmentioning
confidence: 97%
“…9,10 In 1989, Bernard et al 13 described temporary punctal stenting with perforated punctal plugs (PPP) for the treatment of acquired punctal stenosis, and studies evaluating the success rates of PPP reported promising results. 14,15 The aim of this study was to describe the clinical presentations of acquired punctal stenosis, detail our implantation technique, and determine the long-term success rates of PPP for the management of acquired punctal stenosis.…”
mentioning
confidence: 99%